Numerical Assessment Of A Static Mixer Design For Mixing Free Flowing Granular Materials Using The Discrete Element Method - Garneoui, Seifeddine (Journal of Engineering and Technology (JET), 2020)
Mixing is a process of a vital importance in agricultural, chemical and pharmaceutical manufacturing industries, however the behavior of particles during the mixing process still not fully understood as it is related to many physical and process parameters (material type, friction, mixer velocity, etc.). The opposite term of mixing is segregation which might arise during such a mixing process of granular materials and it has a great adverse impact on the mixture. Understanding the flow patterns of granular solids during mixing is a complex and difficult task, therefore deliberating mixing of solid ingredients is a crucial maneuver in the production of powder products. Usually, mixing is conducted via either the rotation of one or several internal rotor(s) (e.g. Screw mixer) or by the rotation of the mixer frame itself (e.g. drum mixer). These mixers require energy dissipated from a motor, in fact, a production line producing batches of products requires much energy and that costs a lot of money. Moreover, appropriate parameters should be set in order to obtain the desired mixture homogeneity that depends on the mixer/rotor(s) rotational speed, mixer/rotor geometry, etc. in this work, a static mixer is designed which has no moving parts, causing mixing by simply filling solid granules. EDEM® software based on Discrete Element Method (DEM) has been utilized to conduct the numerical experiments. Recorded screens of mixing states are used for qualitative assessments, and the Lacey index of mixing has been calculated for every experiment.